Peningkatan Kemampuan Baca Tulis Al-Qur’an (BTQ) bagi Ibu-Ibu Pengajian di Masjid Fastabiqul Khoirot, Desa Sri Pantun, Kecamatan Kongbeng - Binti Fatimatul Khoiriyah; Diva Dhiyaul Auliyah; Zhaniesa Syarfa Taqwa; Abdul Kadir; Anggra Prima (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2026)
This Community Service (PkM) activity was carried out in order to improve the ability to read and write the Qur'an (BTQ) for women attending religious classes at the Fastabiqul Khoirot Mosque. This activity was motivated by the fact that there are still women who are not fluent in reading the Qur'an, both in terms of recognizing Hijaiyah letters and pronouncing them correctly according to Makharijul. The methods used in this activity were short lectures and direct practice in reading the Qur'an. The results showed that 72% of participants experienced improvement in recognizing and pronouncing basic hijaiyah letters after the activity. This activity is expected to provide sustainable benefits for participants and encourage a lifelong passion for learning the Qur'an.